Acute Effects of Levosimendan in Experimental Models of Right Ventricular Hypertrophy and Failure. (1st September 2014) - Vildbrad, Mads D.; Andersen, Asger; Holmboe, Sarah; Ringgaard, Steffen; Nielsen, Jan M.; Nielsen‐Kudsk, Jens Erik
Abstract : Pulmonary arterial hypertension (PAH) is a fatal disease, and the ultimate cause of death is right ventricular (RV) failure. In this study, we investigated the acute hemodynamic effects of levosimendan in two rat models of RV hypertrophy and failure. Wistar rats were randomized to receive sham surgery ( n = 8), pulmonary trunk banding (PTB; n = 8), or monocrotaline injection (MCT; n = 7). RV function was evaluated at baseline and after injection of placebo and two concentrations of levosimendan (12 and 60 μg/kg) using magnetic resonance imaging, echocardiography, and invasive pressure recordings. PTB and MCT injection caused hypertrophy, dilatation, and failure of the RV compared with sham surgery. Levosimendan increased RV end systolic pressure (sham surgery: 16.0% ± 3.8% [ P = 0.0038]; MCT: 9.9% ± 3.1% [ P = 0.018]; PTB: 24.5% ± 3.3% [ P = 0.0001]; mean ± SEM) compared with placebo. Levosimendan markedly increased RV stroke volume (SV) in the MCT group (29.1% ± 8.3%; P = 0.012), did not change RV SV in the PTB group (0.4% ± 4.5%; P = 0.93), and decreased RV SV in the sham surgery group (−10.9% ± 3.7%; P = 0.020). Nitroprusside, which was used to mimic the systemic arterial vasodilator action of levosimendan, did not influence RV function. These data demonstrate that levosimendan acutely improves the failing right heart in a MCT model of PAH and that the mechanism involves a direct acute positive inotropic effect on the hypertrophic and failing RV of the rat.